Clinical Efficiency of Vasopressin or Its Analogs in Comparison With Catecholamines Alone on Patients With Septic Shock: A Systematic Review and Meta-Analysis - Ren-qi Yao; Ren-qi Yao; De-meng Xia; Li-xue Wang; Guo-sheng Wu; Yi-bing Zhu; Hong-qiang Zhao; Qi Liu; Zhao-fan Xia; Chao Ren; Yong-ming Yao (Frontiers Media S.A., 2020)
BackgroundVasopressin is an efficient remedy for septic shock patients as its great capacity in promoting hemodynamic stabilization. The aim of current systematic review and meta-analysis is to compare the clinical efficiency of vasopressin or its analogs with sole catecholamines on patients with septic shock.MethodsA systematic search of Cochrane Library, EMBASE, and PubMed online databases was performed up to 30 Oct 2019 to identify randomized controlled trials comparing use of vasopressin or its analogs (e.g., terlipressin, selepressin) with administration of catecholamines alone.ResultsWe included 23 RCTs with 4,225 patients in the current study. Compared with solely use of catecholamines, administration of vasopressin or its analogs was not associated with reduced 28-day or 30-day mortality among patients with septic shock [RR=0.94 (95% CI, 0.87-1.01), P=0.08, I2 = 0%]. The result of primary endpoint remained unchanged after conducting sensitivity analysis. Despite a significantly higher risk of digital ischemia in patients receiving vasopressin or its analogs [RR=2.65 (95% CI, 1.26-5.56), P < 0.01, I2 = 48%], there was no statistical significance in the pooled estimate for other secondary outcomes, including total adverse events, arrhythmia, acute myocardial infarction (AMI) and cardiac arrest, acute mesenteric ischemia, ICU/hospital length of stay, and mechanical ventilation (MV) duration.ConclusionsThe administration of vasopressin or its analogs was not associated with reduced 28-day or 30-day mortality among patients with septic shock, while an increased incidence of digital ischemia should be noted in patients receiving agonists for vasopressin receptors.